Research priorities for assessing health effects from the Gulf of Mexico oil spill : a letter report (Online access: National Academy of Sciences National Academies Press., 2010)
At the request of the U.S. Department of Health and Human Services (HHS), a committee appointed by the Institute of Medicine (IOM) is tasked with providing advice to HHS on research priorities for assessing health effects of the Gulf of Mexico oil spill. The committee's recommendations are included in this report. The committee believes that it is important to study health effects from the Gulf of Mexico oil spill for three reasons: 1. To learn about the impact of oil spills on human health,2. To improve mitigation efforts, and3. To prevent adverse health effects from occurring in individuals affected by the Gulf of Mexico oil spill and in future disasters. During its information-gathering process, the committee learned about many potential areas of research aimed at improving its understanding of the physical and behavioral health effects of oil spills. All of those areas are important. The committee evaluated the information and narrowed the list of possible research opportunities to those that it believes should be considered priorities. The committee's research priorities encompass five main areas: behavioral health, exposure assessment, seafood safety, communication, and developing a research response framework for disasters. The research priorities, summarized in Box 1, are not presented in any specific order. They address current gaps in knowledge and the order of priority will depend on further scientific review and community input.